2014
DOI: 10.5897/ajmm2010.036
|View full text |Cite
|
Sign up to set email alerts
|

The impact of emotional intelligence on communication effectiveness: Focus on strategic alignment

Abstract: In today's complex communication environment, emotional intelligence, communication effectiveness, and strategic alignment remain a key topic of concern among managers and employees worldwide. Communication effectiveness is a key for organization's performance and progress. The interrelationship between emotional intelligence, communication effectiveness, and strategic alignment plays a vital role in the growth and success of organizations of Iran. Emotional intelligence (EI) and communication effectiveness ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The results of Anna et al, (2012) show a significant relationship between emotional intelligence and decision-making power and emotional intelligence can help a person make difficult decisions. In the study of Hassan et al, (2014), there was a significant relationship between emotional intelligence and communication skills and there was a significant and positive relationship between demographic variables (age and sex) and emotional intelligence.…”
Section: Modabber Arasteh and Seyedeh Asrin Seyedoshohadaeimentioning
confidence: 92%
“…The results of Anna et al, (2012) show a significant relationship between emotional intelligence and decision-making power and emotional intelligence can help a person make difficult decisions. In the study of Hassan et al, (2014), there was a significant relationship between emotional intelligence and communication skills and there was a significant and positive relationship between demographic variables (age and sex) and emotional intelligence.…”
Section: Modabber Arasteh and Seyedeh Asrin Seyedoshohadaeimentioning
confidence: 92%
“…The first 10 questions measure the emotional instability criterion, the second 10 questions emotional return criterion, the third 10 questions social inadaptability criterion, the fourth 10 questions the personality breakdown, and the last 8 questions measure the lack of independence. (11). In addition, this questionnaire was adapted by Iranian culture (5, 15).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies show a significant relationship between emotional quotient and decision-making power, and emotional quotient greatly contributed to the person in difficult decision-making situations. Also, in another study, they concluded that there is a significant relationship between emotional quotient and communication skills (10,11,12).…”
Section: Introductionmentioning
confidence: 98%
“…The emotional factor of character has a great influence on the success of life. Meanwhile, intellectual intelligence only accounts for about 20% for the factors that determine success in life; the other 80% is filled by other forces (Brackett et al, 2011;Gardner & Hatch, 1989;Hassan et al, 2014;Maftoon & Sarem, 2012).…”
Section: Functions Purposes and Impact Of Character Buildingmentioning
confidence: 99%
“…School emphasizes more on the developing academic ability but ignores other development which very large influence on life, even though is it not the only one that determines success (Roeser, Midgley, & Urdan, 1996) (Gross et al, 2015). Intellectual quotients account for only about 20% of the factors that determine success in life, so that 80% is filled by other forces (Brackett, Rivers, & Salovey, 2011;Gardner & Hatch, 1989;Hassan, Saeid, Hashim, Bin, & Khalil, 2014;Maftoon & Sarem, 2012). , issued the words, "The well-being of a nation stems from the strong character of its citizen...".…”
Section: Introductionmentioning
confidence: 99%